2021
DOI: 10.1002/ece3.7911
|View full text |Cite
|
Sign up to set email alerts
|

Eagles enter rotor‐swept zones of wind turbines at rates that vary per turbine

Abstract: Wind energy technology has advanced considerably in past decades (Gibson et al., 2017;Veers et al., 2019), yet ecological challenges such as wildlife fatalities hinder wind power from reaching its full potential (Katzner et al., 2019). There is spatial and temporal variation in these ecological challenges. For example, some individual wind turbines are especially dangerous (i.e., they are identical in form to other nearby turbines, but the location at which they are installed makes them dangerous to volant wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 30 publications
(43 reference statements)
1
31
0
Order By: Relevance
“…(2021), and McClure, Rolek, Braham, et al. (2021) for further details regarding the study site and the configuration and programming of the IdentiFlight system.…”
Section: Methodsmentioning
confidence: 99%
“…(2021), and McClure, Rolek, Braham, et al. (2021) for further details regarding the study site and the configuration and programming of the IdentiFlight system.…”
Section: Methodsmentioning
confidence: 99%
“…The current curtailment prescription at TW applies equally across all turbines (McClure et al . 2021a). Our previous work at TW demonstrated that some turbines were more likely to have eagles enter their rotor‐swept zones than others; therefore, we suggested that curtailment criteria could be tailored for each turbine (McClure et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work at TW demonstrated that some turbines were more likely to have eagles enter their rotor‐swept zones than others; therefore, we suggested that curtailment criteria could be tailored for each turbine (McClure et al . 2021a). In the current study, we also observed variation among turbines (σ C = 0.35; Table 2) in entry probability into the rotor‐swept zone at TW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Site-specific factors also influence a bird's risk of collision within a wind power facility (de Lucas et al, 2008). Indeed, certain turbines present more collision risk than others (McClure et al, 2021b), even under low bird densities (de Lucas et al, 2012). Weak relationships between pre-construction abundance and post-construction mortality at wind power facilities make it difficult to predict where collision risk will be greatest (Ferrer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%